1996
DOI: 10.3382/ps.0750402
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Thermotolerance in Male Broiler Chickens by Temperature Conditioning at an Early Age

Abstract: Chicks were conditioned by exposure to heat stress (36 +/- 1 C; to 80% RH) for 24 h at the age of 5, or 5 and 7 d. During conditioning, weight gain was depressed. Due to accelerated growth during the postconditioning period, a complete compensation for lost weight gain was achieved by the group conditioned at 5 d, but only a partial compensation was obtained in the group conditioned at both 5 and 7 d. At the age of 42 d, challenge with acute heat stress (35 +/- 1 C; 20 to 30% RH) resulted in a large increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
93
1
10

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(119 citation statements)
references
References 17 publications
15
93
1
10
Order By: Relevance
“…In the three experiments, Tb at 7 days of age was reduced by TC as described earlier [11,12] and this reduction remained consistent until the end of the production period, in agreement with earlier findings [3,26,28]. Recent results showed that TC induces the stimulation of gut development and activity, reduces the circulating level of T3 and increases feed intake during the 48 hours following TC [25].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In the three experiments, Tb at 7 days of age was reduced by TC as described earlier [11,12] and this reduction remained consistent until the end of the production period, in agreement with earlier findings [3,26,28]. Recent results showed that TC induces the stimulation of gut development and activity, reduces the circulating level of T3 and increases feed intake during the 48 hours following TC [25].…”
Section: Discussionsupporting
confidence: 77%
“…Short periods of intense heat during the dry season in tropical countries induce major economic losses by increasing late mortality of fast growing broiler chickens. Heat exposure at warm ambient temperature (Ta = 36-38 o C) for 24 hours at 5 days of age, a technique described as "early age thermal conditioning" (TC), durably increases the broiler's resistance to heat stress without negative effects on growth and feed conversion [2,3,26,28]. Similar results have been obtained under real and simulated tropical conditions [10,11] in the laboratory and also under practical broiler production in the tropics [9].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Thermotolerance in birds was achieved by exposing birds to neonatal heat stress (Yahav & Hurwitz 1996). Cyclical higher incubation temperature appears to improve the heat tolerance in chickens (Yahav 2009), depending on the length and period of exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In broiler chickens, exposure to heat (Arjona et al, 1988;Yahav & Hurwitz, 1996;Yahav, 2000). On the other hand, not much research has been conducted to improve thermotolerance at later ages using prenatal but not postnatal heat conditioning (Moraes et al, 2003;2004;Yalçin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%